Two Siblings with Different Presentation of Melas - Low, Qin Jian; Kadzir, Siti Baizura Binti Abdul; Cheo, Seng Wee (Bangladesh Journal of Medicine, 2019)
Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is a rare disease. It is a maternally inherited multisystem disorder caused by mutations of the mitochondrial DNA. MELAS usually occur during childhood period after a normal early development. Commonly, the patients will have a relapsing and remitting course of illness with stroke like episodes and seizures. It will subsequently lead to progressive neurological dysfunction and memory problems. We would like to present two siblings who presented to us with different age of onset and presentation of their illness. Bangladesh J Medicine July 2019; 30(2) : 96-99